Salmonella renal abscess in an immunocompetent child: case report and literature review - Poh, Cedric Wei Ming (2022)
We describe a case of a 10-year-old immunocompetent girl with a left renal abscess due to Group C Salmonella (Salmonella serovar Oranienburg). Percutaneous drainage of the abscess was done. She also received 2 weeks of intravenous ceftriaxone, followed by 4 weeks of oral co-trimoxazole with resolution seen on ultrasound. A review of pediatric Salmonella renal abscesses is also presented.